PRIMORDIAL HELIUM ABUNDANCE BY RRL: NEW RESULT - Tsivilev, A. P.; Sorochenko, R. L.; Cortiglioni, St.; Poppi, S.; Montebugnoli, St. (Одеські астрономічні публікації, 2017)
New results of the Primordial Helium abundance (Yp) measurement by radio recombination lines (RRL) observations from galactic HII regions are presented. The RRL observations were carried out with two Parabolas: RT32(λ = 13.5 mm and 3.5 cm, Medicina, Italy) and RT22 (λ = 8 and 13.5 mm, Pushchino, Russia). The current value was obtained on the base of five source observations with the accurate correction for both the ionization structure and dust influence. At present, the obtained Yp = 25.74(±1.0)value seems to be higher than that suggested by optical data, allowing the presence of unknown light particles, and is in agreement with the result from cosmic microwave background asymmetry.